Prevalence of hepatitis delta virus among chronic hbvcarriers at AOU Federico II. (March 2023) - Cossiga, V.; De Conte, A.; Brusa, S.; Molinari, E.A.; Pignata, L.; Ranieri, L.; Zacchia, E.; Mazzitelli, F.; Guarino, M.; Portella, G.; Morisco, F.
Abstract : Background/Aim: In Italy, the prevalence of HDV infection in HBsAg carriers is about 9.9% (6.4% in Italian natives and 26.4% in immigrants). However, the actual prevalence is probably underestimated because the anti-HDV test is not performed routinely in all HBsAg carriers. The HDV causes a rapidly progressive liver disease and as new antiviral therapies are coming, it is fundamental to known the exact HDV prevalence. The aim of this study was to assess the real HDV prevalence in the AOU Federico II. Methods: From April 2021 to July 2022, reflex test for the detection of total HDV antibodies was performed in all HBsAg positive subjects observed at AOU Federico II. Demographic, clinical and laboratory data were collected. Liver fibrosis was evaluated with FIB-4. Sera were evaluated with ADVIA Centaur HBsAgII Qualitative, Liaison Murex HBsAg Quantitative and Liaison Murex Total Anti-HDV Qualitative. Results: Of 365 HBsAg carriers, 46 (12.6%) resulted positive for total anti-HDV. The majority of them (89.2%) were Italian natives and only 5 (10.8%) of them were immigrants. Twenty-one (45.6%) were males with a median age of 62.2 years. Thirty-five (76%) patients were already aware of HBV/HDV coinfection. HDV-RNA was performed in 18 (39.1%) subjects and resulted detectable in 15 (83.3%) of them, with a median HDV-RNA level of 84.300 [25 th – 75 th percentiles: 1.685-547.796] IU/ml. Twenty (43.5%) anti-HDV positive subjects had advanced liver fibrosis. Conclusions: Our data showed that the HDV prevalence is higher than expected, demonstrating that the reflex test in HBsAg carriers could be a useful approach to identify the real prevalence of HDV infection. Moreover, the HDV-RNA is performed only in the minority of the anti-HDV positive subjects. In this setting, due to the forthcoming approval of specific anti-HDV drugs, a reflex test for HDV-RNA should be implemented to identify viremic patients needing antiviral treatment.